DEVELOPING AN ECO-FRIENDLY CREATIVE TOURISM STRATEGY: A CASE STUDY OF THE THREE-RELIGION, THREE-RIVER COMMUNITY, PHRA NAKHON SI AYUTTHAYA - Karoonyasiri, Nonthalee Boonthad; Treemongkol‬, Patcha; Hongwijit, Suwannee; Meemuk, Nathaphan; Sakdanares, Kessiri; Sansern, Onanong; Soonthondachar, Jaroonsak (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This study investigated the tourism context of a community in Phra Nakhon Si Ayutthaya, uniquely characterized by its heritage of three coexisting religions along three waterways. The primary objectives were to examine the tourism environment in the area, analyze its current conditions, and formulate an environmentally friendly strategy for creative tourism development. A qualitative research methodology was employed for this investigation. The study was conducted in the Khlong Takhian and Samphao Lom sub-districts, with participants selected through purposive sampling. Data collection involved a combination of in-depth interviews, observation, and document analysis. To ensure the reliability of the findings, a triangulation method was used for quality control. The collected data were analyzed using content analysis, guided by the 7Gs Green Tourism framework, which includes principles such as “Green Community” and “Green Responsibility”. A SWOT analysis was then performed to assess the potential of the community, followed by a TOWS Matrix analysis to synthesize the findings into actionable strategies. The results indicate that the community possesses substantial cultural and social capital that aligns well with the principles of Green Tourism. The SWOT analysis highlighted significant strengths, particularly in its strong sense of community and social responsibility. However, a critical weakness was identified in management, stemming from a lack of knowledge in modern tourism practices and the absence of a unified organizational structure. Consequently, seven development strategies were proposed. These strategies focus on leveraging the cultural strengths of the community to create market opportunities. Simultaneously, they aim to address the management knowledge gap through external support and build resilience to preserve the traditional lifestyle of the community.